ANALISIS LAHAN KRITIS DAN ARAHAN REHABILITASI LAHAN DALAM PENGEMBANGAN WILAYAH KABUPATEN KENDAL JAWA TENGAH - Dinik Indrihastuti; Kukuh Murtilaksono; Boedi Tjahjono (Diponegoro University, 2016)
The impact of critical land create reduction quality of soil characteristics, which can interfere with the function of conservation, production, economic, and social life of the community. The objectives of this research are to analyzing and mapping of critical land, reviewing relevance of critical land distribution to the spatial pattern and making direction of rehabilitation in regional development in Kendal. The analytical methode which is used in this study were selecting parameters of critical land and overlay using GIS to map the distribution of critical land. The result of this research is the critical land area in modification parameter is 34.317,87 ha, and parameter of P. 4/V-Set/2013 is 19.535,96 ha. General direction for land rehabilitation is vegetative conservation activity and technical civil conservation for erosion and sedimentation control. Direction for regional development in forest area is to develop PHBM through activity of agroforestry, community forest, ecotourism and medicinal plant cultivation in the forest. Direction on the farm cultivation area, especially on abandoned land and yards, is by optimization of community forest, by planting activities using perennials plant, MTPS and fruits plant, to control critical land, soil conservation and water management as well as increase community incomes by selling products from community forests.